PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS), PRICE BOOK VALUE (PBV), DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN SAHAM - Fransiska Sepriana; Saryadi Saryadi (Universitas Diponegoro, 2018)
When an investor wants to make an investment, investor should consider the things that can affect the return. The technical and fundamental analysis has become a solution for the investor to predict the stocks’ price. Specifically, this study discusses about fundamental analysis by appraising the companies’ performance which is depicted on the companies’ financial report with ratio as a tool to analyze the financial report. This study aimed to analyze the influence of Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), Price to Book Value (PBV) and Debt to Equity Ratio (DER) either partially or simultaneously toward Stock’s return on property & real estate companies sector listed in Indonesia Stock Exchange period 2012 -2016. The data used in this analysis is the reference point secondary data in the form of financial report published by IDX. The samples in this study were 33 property and real estate sub-sector companies. Analysis technique used in this research are simple and multiple linear regression.Results of the study stated that partially ROA, ROE, and EPS have significant effect on stock return. PBV and DER has no significant effect on stock return, and simultaneously there was significant influence between ROA, ROE, EPS, PBV, and DER to stock return and it is found that EPS has dominant influence to the stock return.It is recommended that property and real estate sub-companies can maintain returns by improving strategy and cost efficiency in order to increase profitability, and using earning per share ratios in performing company performance analysis.